1968
DOI: 10.4319/lo.1968.13.4.0637
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF HYDROSTATIC PRESSURE ON SYNTHESIS OF PROTEIN, RIBONUCLEIC ACID, AND DEOXYRIBONUCLEIC ACID BY THE PSYCHROPHILIC MARINE BACTERIUM, VIBRIO MARINUS1

Abstract: The temperature and hydrostatic pressure maxima for growth of the marine psychrophilic bacterium, Vibrio marinus MP-4, were 20C and 425 atm. The effects of pressures of 206, 400, 500, and 1,000 atm at 15C on synthesis of net protein, RNA, and DNA by growing cells of V. murinus Ml?-4 were determined.A pressure of 1,000 atm completely inhibited protein and DNA synthesis but allowed RNA synthesis to continue for a short time. At 200 atm, the rates of protein and RNA synthesis decreased for approximately 60 min an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…While the study of piezophiles may reveal novel cellular mechanisms supporting life in the deep biosphere, the study of piezotolerant and piezosensitive bacteria may highlight the most sensitive pathways affected by hydrostatic pressure. Albright and Morita 32 found that in the psychrophilic marine bacterium Vibrio marinus the rate of protein and RNA synthesis was affected after being exposed to 20 MPa for 60 min, although 1-atm rates were resumed shortly afterwards. Turley 33 observed reduced uptake of 3 H-thymidine and 3 H-leucine for microbial protein synthesis between 0.1 and 43 MPa, but no effect on cell abundance.…”
Section: Discussionmentioning
confidence: 99%
“…While the study of piezophiles may reveal novel cellular mechanisms supporting life in the deep biosphere, the study of piezotolerant and piezosensitive bacteria may highlight the most sensitive pathways affected by hydrostatic pressure. Albright and Morita 32 found that in the psychrophilic marine bacterium Vibrio marinus the rate of protein and RNA synthesis was affected after being exposed to 20 MPa for 60 min, although 1-atm rates were resumed shortly afterwards. Turley 33 observed reduced uptake of 3 H-thymidine and 3 H-leucine for microbial protein synthesis between 0.1 and 43 MPa, but no effect on cell abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of the dissociation process masks the effect of pressure on association. DISCUSSION The relevance of results obtained with a cell-free system to the functioning of an intact living cell has been approached by comparing the effects of pressure on protein synthesis in various kinds of cells (1,3,(5)(6)(7) with the results of this study. The comparison is shown in Fig.…”
Section: Figure~7mentioning
confidence: 99%
“…The effects of high hydrostatic pressures on macromolecular synthetic processes (i.e., protein, DNA, and RNA synthesis) have been studied recently in our laboratory and elsewhere (1)(2)(3)(4)(5)(6)(7)(8) with the general conclusion that rates of synthesis are reduced by pressure in both bacterial and mammalian cells. In all cases, protein synthesis was found to be the most pressure sensitive, followed by DNA, and least sensitive RNA synthesis (3,6,7). In view of these findings, we thought it worthwhile to study the effect of pressure on synthesis in cell-free systems.…”
Section: Introductionmentioning
confidence: 99%
“…At 600 atm, under the same conditions, 23 of the 56 species that failed to grow were killed. There are many reasons presented as to why hydrostatic pressure adversely affects bacteria, including the interruption of energy production due to pressure (3), molecular volume changes that affect enzyme reaction rates (2,5,6,9,12,13,15), and loss of the ability to synthesize macromolecules (1,10,11,17). Molecular volume decreases with de-creasing temperature and with increasing pressure.…”
mentioning
confidence: 99%